Influence of histocompatibility genes on disease susceptibility and treatment response in patients with relapsing-remitting multiple sclerosis treated with interferon beta-1a - Shlomo Flechter; Tirza Klein; Lea Pollak (MDPI AG, 2011)
Multiple sclerosis (MS) is the most common, non-traumatic cause of neurological disability in young adults. The aim of this study was to investigate the influence of HLA class II alleles DRB1* and DQB1* on susceptibility to relapsing-remitting (RR) MS and response to interferon (IFN) beta-1a treatment. A prospective observational study was conducted. Seventeen patients with clinically definite RRMS, attending a tertiary referral center for multiple sclerosis in Israel and receiving treatment with subcutaneous IFN beta-1a, 22 mcg three times weekly were recruited between December 1998 and February 2000 and observed for 12 months. HLA genotyping was performed and clinical characteristics (relapse rate and disability progression) assessed at baseline and after 12 months. HLA data for a healthy control group were also used for comparison. HLA and the success of treatment with IFN beta-1a in this group of RRMS patients were assessed. The frequency of DRB1*03 was six times higher in patients treated with IFN beta-1a than in the healthy control group (n = 100): 29% (5/17) versus 5% (5/100), respectively. Additionally, DQB1*03 and DQB1*02 were present in 82% (14/17) and 41% (7/17) of RRMS patients, but in only 33% (33/100) and 18% (18/100) of control patients, respectively. A better response to IFN beta-1a treatment was seen in patients carrying these alleles than in patients without these alleles. Our results indicated that DRB1*03, DQB1*03 and DQB1*02 alleles may contribute to MS susceptibility and IFN beta-1a responsiveness, and warrant further verification in a larger population.